Forecasting exchange rates of major currencies with long maturity forward rates - Zsolt M. Darvas; Zoltán Schepp (Bruegel, 2020)
This paper presents unprecedented exchange rate forecasting results, based upon a new model that approximates the gap between the fundamental equilibrium exchange rate and the actual exchange rate with the long-maturity forward exchange rate. The theoretical derivation of our forecasting equation is consistent with the monetary model of exchange rates. Our model outperforms the random walk in out-of-sample forecasting of twelve major currency pairs over the short and long horizon forecasts for the 1990-2020 period. The results are robust for all sub-periods, with the exception of the years around the collapse of Lehman Brothers in September 2008. Our results are robust to alternative model specifications, single equation and panel estimation, recursive and rolling estimation, and alternate data construction methods. The model performs better when the long-maturity forward exchange rate is assumed to be stationary, as opposed to assuming non-stationarity. The improvement in forecast accuracy from our model is economically and statistically significant for almost all exchange-rate series. The model is simple, linear, easy to replicate, and the data we use is available in real time and not subject to revision.
Keywords: F31; F37; 330; exchange rate; error correction; forecasting performance; monetary model; out-of-sample; random walk